2013
DOI: 10.2135/cropsci2012.01.0039
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide Association Study for Beta‐glucan Concentration in Elite North American Oat

Abstract: Genome‐wide association studies (GWAS) can be a useful approach to detect quantitative trait loci (QTL) controlling complex traits in crop plants. Oat (Avena sativa L.) β‐glucan is a soluble dietary fiber and has been shown to have positive health benefits. We report a GWAS involving 446 elite oat breeding lines from North America genotyped with 1005 diversity arrays technology (DArT) markers and with phenotypic data from both historical and balanced 2‐yr data. Association analyses accounting for pair‐wise rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The percentages are very close to the results from a previous study in oat (8.9% and 5.5%) [8], where the material consisted of oats from multiple breeding programs. Other studies on population structure in oat have found the same level of variation within the first PCs as well [84,99,123]. In our study, most studied lines were breeding lines from a breeding program, supplemented with a few accessions from the gene bank and other breeding programs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The percentages are very close to the results from a previous study in oat (8.9% and 5.5%) [8], where the material consisted of oats from multiple breeding programs. Other studies on population structure in oat have found the same level of variation within the first PCs as well [84,99,123]. In our study, most studied lines were breeding lines from a breeding program, supplemented with a few accessions from the gene bank and other breeding programs.…”
Section: Discussionsupporting
confidence: 56%
“…DON content had as well significant associations with multiple markers on merged linkage groups 03/4C, 09/6C, 18, 23/11A and 28 [81] (7C-17A) [82]. Other GWAS studies made in oats are for beta-glucan [83,84], crown rust [85], lodging, plant height [86] and frost tolerance [87]. All of these studies implicate that oat generally has less genetic variation and a weak population structure compared to other cereals.…”
Section: Introductionmentioning
confidence: 93%
“…It was shown that LD in oat extended over shorter distances compared to barley, was relatively consistent across most germplasm clusters and was mostly free of major population structure other than distinction between spring and winter types (Newell et al., ). Subsequently, GWAS was successfully used to identify marker associations with beta‐glucan concentration in globally collected oat (Newell et al., ) as well as within elite North American oat varieties (Asoro, Newell, Scott, Beavis, & Jannink, ). GWAS of FHB resistance has been reported in wheat (Kollers et al., ) and barley (Massman et al., ), but not in oat.…”
Section: Introductionmentioning
confidence: 99%
“…With the advance of high throughput, cost‐effective marker genotyping platforms, AM has proved to be a powerful genomic tool for whole genome analysis and genetic dissection of complex traits in crop species (Huang et al, 2010; Jia et al, 2013; Li et al, 2013; Mamidi et al, 2011). Given high‐density marker panels, AM provides an opportunity to identify QTL at a higher mapping resolution by taking advantage of historical linkage disequilibrium (LD) with diverse germplasm collections including unstructured populations from breeding programs (Asoro et al, 2013; Mamidi et al, 2011; Sukumaran et al, 2012). In the University of Minnesota soybean breeding program, rhg1 is the only known resistance gene characterized and deployed in the germplasm collection.…”
mentioning
confidence: 99%